Chaetoceros resting spores in the Gerlache Strait, Antarctic Peninsula - Ferrario, Martha Elba (1998)
The formation of resting spores in diatoms is a common phenomenon in neritic environments. Here we report on resting spores of the genus Chaetoceros associated with a layer of increased chlorophyll fluorescence, at a depth of more than 200 m, north of Brabant Island and in Wilhelmina Bay, southeast coast of the Gerlache Strait (64°41.0′S, 62°0.5′W). Six species of Chaetoceros were identified by the morphology and size of the resting spores. Given that Chaetoceros spp., both in vegetative cells and as resting spores, are commonly found in Antarctic coastal surface waters, their location at depth could represent the pelagic “waiting” or “seeding” populations mentioned for other environments.